PENEGAKAN HUKUM TINDAK PIDANA DALAM PEMILIHAN KEPALA DAERAH BUPATI DAN WALIKOTA DI PROVINSI RIAU TAHUN 2017 - Putra, Yogi Rahmadani; Indra, Mexsasai; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Elections are a form of democracy, but in elections as a manifestation of democracy the regional head elections that took place in Riau Province in 2017 were accompanied by violations of the law, especially criminal law by using ballots more than once. In the judicial process, there are so many resolutions up to the Supreme Court, so that it becomes a manifestation of the failure of the district court in providing justice to the community.The formulation of the problems used in the writing of this thesis are: First, how is the criminal law enforcement of the Regional Head Election of Regents and Mayors in Riau Province in 2017. Second, Obstacles in law enforcement for the criminal act of Regional Head Election of Regent and Mayor in Riau Province in 2017. Third, Efforts to overcome barriers to law enforcement in the election of regional heads of regents and mayors in Riau Province in 2017. The type of research used in this research is sociological law research. Sources of data used in this study are primary legal materials, secondary legal materials and tertiary legal materials. The data collection technique was carried out by two methods, namely interviews and literature studies.From the results of the study, it was found that, first, in law enforcement the criminal act of the Regional Head Election of Regents and Mayors in Riau Province in 2017 carried out by an integrated law enforcement center in Riau Province was still ineffective because of the many cases handled there were only 9 (nine) cases that arrived at At the court level, as well as in the handling of disagreements, there are often disagreements that lead to debates between integrated law enforcement centers in determining cases of criminal violations in regional head elections. Second, obstacles to the enforcement of criminal law in the Regional Head Elections for Regents and Mayors in Riau Province in 2017, namely, Lack of coordination at the Gakkumdu center, a relatively short time limit in determining a criminal case for regional head elections, people who are less active in reporting violations of head elections area and the lack of facilities and infrastructure for the center of Gakkumdu. Third, efforts to overcome obstacles to law enforcement in the election of regional heads of regents and mayors in Riau Province in 2017, namely improving the quality of personnel, conducting socialization to the community, utilizing the available infrastructure.Keywords: Law Enforcement – Gakkumdu – Criminal Act on Election